2020
DOI: 10.1142/s0192415x20500135
|View full text |Cite
|
Sign up to set email alerts
|

Research Advances on Acupuncture Analgesia

Abstract: Pain is a widespread and complex symptom which causes serious emotional and social burdens to individuals and society. Most patients with pain rely heavily on over the counter (OTC) and prescription pain killers. However, there would be a number of issues that arise from the use of pain killers, in which safety and addiction are the most critical issues. For traditional Chinese medicine (TCM), pain is a result of the meridians being blocked. This could occur as a symptom of or be caused by various diseases. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 55 publications
1
51
0
Order By: Relevance
“… 44 , 45 This conventional therapy achieves pain intensity during OPU by suppressing the endogenous opioid system, increasing endogenous opioid peptide release, reducing inflammation, and improving uterine blood flow changes. 6 , 46 , 47 In this review, Fan 35 and Tian et al 37 found significantly higher β-endorphin in the acupuncture group than the control groups (P<0.05). We also discovered that acupuncture is a safe analgesic approach since there were no differences between groups about the number of oocytes retrieved 27 , 28 , 30–32 , 34 , 35 or clinical pregnancy 30–32 , 35 , 36 after the procedure.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“… 44 , 45 This conventional therapy achieves pain intensity during OPU by suppressing the endogenous opioid system, increasing endogenous opioid peptide release, reducing inflammation, and improving uterine blood flow changes. 6 , 46 , 47 In this review, Fan 35 and Tian et al 37 found significantly higher β-endorphin in the acupuncture group than the control groups (P<0.05). We also discovered that acupuncture is a safe analgesic approach since there were no differences between groups about the number of oocytes retrieved 27 , 28 , 30–32 , 34 , 35 or clinical pregnancy 30–32 , 35 , 36 after the procedure.…”
Section: Discussionmentioning
confidence: 69%
“…Acupuncture has been widely used during long periods for analgesia. 6 , 7 Prolonged clinical practice proved acupuncture compound analgesia therapy in OPU has the advantages of safety, high efficiency, fast recovery, and few side effects. 8 , 9 Although previous systematic review 10 demonstrated no evidence supporting acupuncture to be more optimal for pain relief during OPU than PCA with CSA, the updated Cochrane review supported acupuncture is appropriate to adjuvant analgesia OPU process.…”
Section: Introductionmentioning
confidence: 99%
“…Analgesia derives from integrated mechanisms involving the nervous system, the painful stimuli, and the stimuli resulting from skin infission with needles. Several neurotransmitters are involved, including serotonin, adenosine, gamma-aminobutyric acid, opioid peptides, calcitonin gene-related peptide, and substance P [ 28 ]. The above list of substances involved in acupuncture-induced analgesia is certainly not exhaustive, but the molecules act through pathways involving segmental and supraspinal spinal mechanisms [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through a large number of clinical studies, it is found that acupuncture at Baihui and Neiguan Points has a significant effect on improving brain hypoperfusion, enhancing brain metabolic function, enhancing brain blood flow and restoring brain nerve cell function. In addition, acupuncture at Zusanli and Hegu can also be used during practical application, in which acupuncture at Zusanli can activate most brain regions, including frontal lobe, temporal lobe, insular lobe and part of cerebellum [7] . Among them, the most significant effect is to stimulate the temporal lobe region of the brain.…”
Section: Discussionmentioning
confidence: 99%